Numerical investigations on entropy generation in cross-wavy channels. (January 2020) - Shi, Xusheng; Wang, Yongwei; Huai, Xiulan
Abstract: The numerical study to research the influence of ratio of channel amplitude to pitch of cross-wavy on entropy generation is conducted in this paper. In Reynolds number range of 200-1200, five types of cross-wavy channel are analyzed. The simulation results show the thermal entropy generation rising rate is fast when Reynolds number less than 700 and then flat. In addition, it is smaller with increasing channel amplitude to pitch value. The frictional entropy generation increases almost linearly with Reynolds number. However, it is much less than thermal entropy generation under the same conditions. In brief, the channels which have larger ratio of amplitude to pitch can reduce the total irreversibility to the least under the same flow conditions.